The role of religion when crisis looms: A church community at a crossroads - Trueman, Lauren (Journal of religion, spirituality & aging, 2017)
The present study examined the relationship between religion and well-being in older adults during a time of financial difficulty within their religious community. Focus-group and one-on-one interviews were carried out with 39 participants sampled from three Anglican parishes in eastern Canada during a financial crisis that was likely to lead to the closing of two churches. Three main themes emerged from the analyses: Crisis, Transition, and Status Quo. The financial situation was discussed as a crisis; other issues were viewed as opportunities for transition, and personal faith was perceived as being stable and constant. The results of the present study suggest that for older adults, the more internal and faith-based aspects of religiosity have a stronger impact on well-being than do changes that revolve around the external or religious aspects of church participation.